Suicidal ideation and interrelated psychiatric disturbances in rheumatoid arthritis: Evidence from a Vietnamese cohort - Ha Thi Thu Tran; Tam Minh Duong; Tuan Van Nguyen; Ha Thi Thu Le; Hue Thi Doan; Yen Hoang Nguyen; Hoa Thi Nguyen; Long Thanh Nguyen; Thang Xuan Pham; An Thi Ha Tran; Phi Van Nguyen; Son Truong Hoang; et al. (PLoS ONE, 2026)
Objective This study aimed to determine the prevalence of suicidal ideation among Vietnamese patients with rheumatoid arthritis (RA), and to examine associated factors, other psychiatric disturbances, and quality of life (QoL). Methods A cross-sectional study was conducted from June 2024 to December 2024 at Bach Mai Hospital, Hanoi. Eligible patients met the 1987 ACR classification criteria for RA. Suicidal ideation was assessed through structured psychiatric interviews. Depression, anxiety, insomnia, and sexual dysfunction were evaluated using the PHQ-9, HAM-A, ISI, and ASEX, respectively, while QoL was measured with the EQ-5D-5L. Correlation analyses and structural equation modeling (SEM) explored interrelationships among psychiatric disturbances. Multivariable regression was applied to identify predictors of suicidal ideation, psychiatric symptoms, and QoL. Results Among 187 participants (mean age 56.9 ± 12.7 years; 84.0% female), 13.4% reported suicidal ideation. Anxious (45.5%), insomnia (48.1%) and depressive symptoms (28.3%) were highly common, and depressive, anxiety, and insomnia symptoms were strongly interrelated (e.g., r = 0.74–0.80). The mean EQ-5D-5L index value was 0.6 ± 0.2, indicating moderate impairment in overall QoL. SEM confirmed high correlation between psychiatric (DEP, ANX) and behavioral (SLP, SEX) disturbances. Multivariable analysis showed that high disease activity, joint deformity, and treatment-related adverse effects were consistently associated with suicidal ideation, psychiatric symptoms, and impaired QoL. Conclusion Suicidal ideation and other psychiatric disturbances are commonly observedamong patients with RA in Vietnam. Disease activity, structural damage, and medication-related adverse effects were major determinants, underscoring the need for integrated mental health screening and multidisciplinary management to optimize both clinical and psychosocial outcomes.